(untitled) (Journal of Atomic and Molecular Sciences, 2014)
The main aim of this paper is to discuss the electrodynamics of relativistic dynamics of particles bases on the notion of the non-standard Lagrangians which have gained increasing importance in the theory of nonlinear differential equations, dissipative dynamical systems and theoretical physics. The mathematical settings are constructed starting from the modified Euler-Lagrange equation and modified Hamiltons equations. Some illustrative examples are considered and discussed.